2008
DOI: 10.3327/jnst.45.1036
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Degradation Assessment in Pressure Vessel Steel by Harmonic Generation Technique

Abstract: The harmonic generation technique has been used to characterize the isothermal degradation of pressure vessel steel. The isothermal degradation was conducted at 630 C with forged 2.25Cr-1Mo steel. The variation in the normalized ultrasonic nonlinearity parameter (= 0 ) was interpreted as having resulted from microstructural evolution, which was supported by the results of electron microscopy and X-ray diffraction, in addition to Vickers hardness and ductile-brittle transition temperature. The normalized ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The lattice parameter of the M 23 C 6 phase increased slightly from 1.0650 nm for the material service-exposed for 54,750 h to 1.0660 nm for the material exposed for 68,550 h. The diffusion of the alloying element Cr led to its replacement of Fe within the M 23 C 6 phase, which increased the lattice parameter of the M 23 C 6 phase as service time increased. Changes in the M 23 C 6 lattice parameter as a function of aging time have also been reported for other steels, including 2.25Cr-1Mo [30] and P91 [31]. However, the peaks of specific precipitated phases were difficult to record because of their low intensity and overlap with the peaks of other phases.…”
Section: Phase Changesmentioning
confidence: 66%
“…The lattice parameter of the M 23 C 6 phase increased slightly from 1.0650 nm for the material service-exposed for 54,750 h to 1.0660 nm for the material exposed for 68,550 h. The diffusion of the alloying element Cr led to its replacement of Fe within the M 23 C 6 phase, which increased the lattice parameter of the M 23 C 6 phase as service time increased. Changes in the M 23 C 6 lattice parameter as a function of aging time have also been reported for other steels, including 2.25Cr-1Mo [30] and P91 [31]. However, the peaks of specific precipitated phases were difficult to record because of their low intensity and overlap with the peaks of other phases.…”
Section: Phase Changesmentioning
confidence: 66%
“…The ultrasonic NDE technique has been broadly applied to characterize materials, with many theoretical and experimental investigations in the literature. 5,6 When an ultrasonic sinusoidal wave is introduced into an anharmonic solid, the fundamental wave may be distorted as it propagates so that the second and higher harmonics of the fundamental frequency will be generated. The contact nonlinearity is caused by the nonlinearity in the stress-strain relation across the interface (i.e., voids, cracks, delamination and disbonds) due to the difference of reflection and transmission in the interface region.…”
Section: Introductionmentioning
confidence: 99%
“…However, the changes in nonlinearity are not well understood, nor is the cause of the embrittling effects during the aging process [14]. Kim and Park reported that variation in ultrasonic nonlinearity results from microstructural evolution of 2.25Cr-1Mo steel, and this conclusion was supported by the results of electron microscopy and X-ray diffraction in addition to the Vickers hardness and ductile-brittle transition temperature [15].…”
Section: Introductionmentioning
confidence: 99%